Flexible operation of switchable chlor-alkali electrolysis for demand side management. (1st December 2019) - Roh, Kosan; Brée, Luisa C.; Perrey, Karen; Bulan, Andreas; Mitsos, Alexander
Graphical abstract: Highlights: Economic potentials of the switchable chlor-alkali electrolysis are analyzed. Optimal operation and oversizing of the electrolyzers are determined simultaneously. A decomposition algorithm based on GGS is used for optimal oversizing. The switchable operation is capable of reducing electricity use as well as costs. Abstract: Flexible operation of chlor-alkali electrolysis is a novel strategy for minimizing electricity costs in electricity markets with volatile prices. We recently proposed an operation strategy to adjust the process to electricity price profiles by varying the load and by switching the operation between two different modes (Brée et al., 2019). This flexible operation leads to savings in operating costs but to increased capital investment due to retrofitting for overcapacity and/or switchable operation. Here, we solve an optimization problem which determines optimal operation and (if necessary) oversizing of the switchable chlor-alkali process. This optimization allows analyzing the electricity utilization as well as economic potential of the flexible operation. To arrive at the optimum in reasonable computation time, we use a piecewise linear model for the power demand calculation. Moreover, we use a decomposition algorithm based on the golden-section search of the complicating variable representing oversizing. We show that the flexible operation is capable of reducing electricity utilization as well as costs. Higher savings in the operating costs can be gained with a stronger electricity price fluctuation, a larger operational margin, a bigger chlorine storage tank, and lower capital investment for retrofitting. Lastly, electrolyzer lifetime reduction due to the flexible operation somewhat increases investment costs and thus slightly diminishes cost savings.